2017
DOI: 10.1016/j.watres.2017.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Palladized cells as suspension catalyst and electrochemical catalyst for reductively degrading aromatics contaminants: Roles of Pd size and distribution

Abstract: a b s t r a c tThe palladized cell (Pd-cell) could be used as an efficient catalyst in catalyzing the degradations of a wide variety of environmental contaminants. Nevertheless, when the Pd NPs associate with the bacteria, the catalytic activity likely significantly affected by the biomass. Quantitative indicators that characterize of Pd-cell are necessary and little attention has been paid to investigate how the catalytic efficiency of Pdcell is affected by the size and distribution of Pd NPs. To fill this ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Conversely, the best electrocatalytic effect was achieved on electrodes covered with Pd@cells with nanoparticles of size greater than 50 nm. [ 81 ] Following the results obtained in the previous study, Cheng and colleagues demonstrated that the electrocatalytic activity of S. oneidensis @Pd biofilm formed on the surface of an electrode can be increased 68 times upon hybridization with carbon nanotubes (in a 1: 10 ratio Pd /CNT). The hybridized CNT acts as an electron bridge improving the electron transfer throughout the growing biofilm, thus increasing the current density from 0.02 mA cm −2 (Pd@cells) to ≈0.1 mA cm −2 (Pd@cell@CNTs10).…”
Section: Nanoenzyme Tailoring and Synthesismentioning
confidence: 83%
“…Conversely, the best electrocatalytic effect was achieved on electrodes covered with Pd@cells with nanoparticles of size greater than 50 nm. [ 81 ] Following the results obtained in the previous study, Cheng and colleagues demonstrated that the electrocatalytic activity of S. oneidensis @Pd biofilm formed on the surface of an electrode can be increased 68 times upon hybridization with carbon nanotubes (in a 1: 10 ratio Pd /CNT). The hybridized CNT acts as an electron bridge improving the electron transfer throughout the growing biofilm, thus increasing the current density from 0.02 mA cm −2 (Pd@cells) to ≈0.1 mA cm −2 (Pd@cell@CNTs10).…”
Section: Nanoenzyme Tailoring and Synthesismentioning
confidence: 83%
“…These particles possessed a larger average size of 25.8 nm, but with high exposed surface area, extracellular distribution, and cell surface coverage, indicating that these properties were more favourable than size. 96 At lower CDW : Pd ratios there were fewer cell nucleation sites and the cells were exposed to more metal toxicity. The particles were larger and more often extracellular, as they nucleated in the periplasm then grew beyond the cell surface; in addition damaged cells would release enzymes providing additional extracellular nucleation sites, and abiotic reduction would occur.…”
Section: Bio-pd From Microbial Bioreductionmentioning
confidence: 99%
“… 95 Hou et al also showed that the CDW : Pd ratio affected the extracellular distribution of bio-Pd, which in turn impacted the catalytic activity of bio-Pd nanoparticles. 96 Pd/ S. oneidensis nanoparticles were synthesised using formate as the electron donor at five different CDW : Pd ratios: 6 : 1, 3 : 1, 1 : 1, 1 : 3 and 1 : 6, which increased the average particle size from <10 nm to >50 nm. When tested as a suspension catalyst for the reduction of nitrobenzene and 4-chlorophenol, the smallest nanoparticles gave some of the lowest rates of reaction.…”
Section: Bio-pd From Microbial Bioreductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the feasibility of Pd NPs production has been demonstrated in a number of bacteria, including Shewanella 9 , Geobacter 10 , Desulfovibrio 11 , Enterococcus 12 , etc. Efforts to improve the catalytic activity of bio-Pd have been made by controlling the size and distribution of Pd NPs or by introducing another metal to form Pd based bimetal NPs 13 , 14 . In addition, to avoid the loss of bio-Pd, magnetite was proved to be co-deposited with Pd on the cell and facilitated the its recovery 6 .…”
Section: Introductionmentioning
confidence: 99%